2021
DOI: 10.3389/fonc.2021.710689
|View full text |Cite
|
Sign up to set email alerts
|

Siglec-15 Promotes Tumor Progression in Osteosarcoma via DUSP1/MAPK Pathway

Abstract: Recurrence and metastasis are important features of osteosarcoma (OS) that cause its poor prognosis. Aberrant expression of Sialic acid-binding immunoglobulin-like lectin 15 (Siglec-15) has been reported in various kinds of cancers. However, the expression and function of Siglec-15 in OS remain unclear. In cultured OS cells (143B cells and MNNG/HOS cells) and their xenograft mouse models, we found that downregulation of Siglec-15 could inhibit the proliferation, migration and invasion of by inducing epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 59 publications
3
37
0
Order By: Relevance
“…This gave us a hint that p38-MAPK may be involved in the regulation of cell migration and invasion by Ang2. MAPK pathway, as a key signal pathway affecting cell migration and invasion, plays a role by responding to extracellular stimuli [30] . In the process of in ammation, the p38-MAPK signaling pathway has been con rmed to be activated by IL-1β to promote in ammation [12] .…”
Section: Discussionmentioning
confidence: 99%
“…This gave us a hint that p38-MAPK may be involved in the regulation of cell migration and invasion by Ang2. MAPK pathway, as a key signal pathway affecting cell migration and invasion, plays a role by responding to extracellular stimuli [30] . In the process of in ammation, the p38-MAPK signaling pathway has been con rmed to be activated by IL-1β to promote in ammation [12] .…”
Section: Discussionmentioning
confidence: 99%
“…TAM-associated Siglec-15 can promote tumor immune escape by suppressing CD8 + T-cell responses and promoting immunosuppressive TME formation through the production of transforming growth factor-β (TGF-β) [ 29 ]. In addition, recent studies have shown that Siglec-15 promotes the malignant progression of osteosarcoma (OS) cells by inhibiting the DUSP1-mediated mitogen-activated protein kinase (MAPK) pathway, and high expression of Siglec-15 is associated with pulmonary metastasis and predicts poor prognosis in OS patients [ 39 ]. Li et al suggested that Siglec-15 presented immunosuppressive relevance in pancreatic ductal adenocarcinoma (PDAC) and was expressed on TAMs and PDAC cells.…”
Section: Expression Spectrum Of Siglecs In Tumorsmentioning
confidence: 99%
“…Each Siglec preferentially recognizes a different type of sialic acid. Siglec-15, in particular, is selectively expressed in myeloid cells and osteoclasts [45] . While studies in other types of sarcoma are lacking, preclinical studies on osteosarcoma cell lines and xenograft mouse models discovered that downregulation of Siglec-15 led to decreased tumor proliferation by inducing EMT and promotion of DUSP1 [46] .…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…Siglec-15, in particular, is selectively expressed in myeloid cells and osteoclasts [ 45 ] . While studies in other types of sarcoma are lacking, preclinical studies on osteosarcoma cell lines and xenograft mouse models discovered that downregulation of Siglec-15 led to decreased tumor proliferation by inducing EMT and promotion of DUSP1 [ 46 ] . Following that finding, an analysis of 36 human osteosarcoma samples also showed that higher expression of Siglec-15 by immunohistochemistry was associated with worse overall survival compared with tumors with low Siglec-15 expression [ 46 ] .…”
Section: Emerging Mechanisms Of Resistancementioning
confidence: 99%